(untitled) (Zoological Records and Reviews, 2023)
Habitat fragmentation – the process by which continuous habitat is divided into smaller, isolated patches surrounded by a matrix of modified land – affects animal populations not only through direct reduction of available habitat area but through behavioural changes that alter movement decisions, foraging strategies, social structure, mating patterns, and stress physiology in ways that may precede and predict population-level decline. This review synthesises evidence from 196 primary studies (2005-2023) examining the behavioural responses of European vertebrates to habitat fragmentation across terrestrial, freshwater, and coastal ecosystems, evaluating six major behavioural domains: movement and dispersal, foraging and diet, social organisation, reproductive behaviour, stress physiology, and anti-predator behaviour. Movement responses to fragmentation are the most extensively documented: GPS telemetry studies show that 68.4% of European forest mammals increase their mean daily movement distances in fragmented landscapes (mean increase 42.4 +- 12.4% vs. continuous forest reference), while simultaneously reducing matrix crossing frequency – indicating movement cost avoidance that compounds patch-level isolation. Chronic stress responses – elevated faecal glucocorticoid metabolites at fragment edges and in small isolated patches – are documented in 14 European mammal and bird species, with stress levels inversely correlated with patch size and positively correlated with edge density. Behavioural responses vary substantially by taxon, matrix permeability, and landscape context, generating a complex interplay between individual behavioural adaptation and population-level vulnerability. Implications for wildlife corridor design, connectivity conservation, and fragmented landscape management under EU Nature Restoration Law are discussed.